Formation the Capitalist Economy Perspective of the Turkish Conservative - YILMAZ, Levent (International Journal of Contemporary Economics and Administrative Sciences, 2020)
Turkey’s modernization process can be traced back to the mid-18th century. Turkey is precisely in this process (since the early 19th century) began to enter into an intense relationship with the capitalist countries. However, this form of relationship develops within the framework of unilateral dependence. These relations transformed with the Republic Revolution; new Turkey’s relations with the capitalist countries, has established within the framework of the modern rules. Conservative thinking has also been heavily influenced by these historical conditions. In Turkey, we can talk about two central conservative veins, which developed in the 100 to 150 years: The center-right that adopts the rules of capitalism and the radicals against capitalism.